Early Childhood Science Learning with Models Learning Children Learning in Science - Ayu Pratamawati (Universitas Muhammadiyah Enrekang, 2022)
Science learning activities for early childhood should be carried out in a fun way, bringing children closer to nature, developing thinking skills and science process skills. One of the recommended learning models is the Children Learning in Science learning model. This study aims to analyze early childhood science learning using the Children Learning In Science learning model. This research is a literature review study using the Google Scholar search engine with a total of 76 articles. The results obtained were 10 articles that met the inclusion and exclusion criteria. The results of the study found three themes, namely early childhood science, children learning in science learning models, and the application of children learning in science learning models in early childhood science learning. Science learning should be instilled from an early age. Science learning for early childhood includes products, processes and science attitudes. With this learning model, early childhood can learn science as a whole and in accordance with the principles of early childhood science learning, namely concrete and fun.